Juridical Review of Force Majeure Clause in Credit Bank Agreements when Covid-19 Disaster - Abdul Rahman; Taufan Fajar Riyanto; Siti Rodhiyah Dwi Istinah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The Covid-19 pandemic has occurred since the beginning of 2020 which has had an impact on various sectors of human life, both health, social and economic. One of the sectors most affected by the COVID-19 pandemic is banking due to the large number of non-performing loans during the pandemic. Based on this situation, the government issued Presidential Decree no. 12 of 2020 concerning the Determination of Non-Natural Disasters for the spread of covid-19. Based on this background, the problems in this study will raise the juridical study of whether the covid-19 pandemic can be said to be force majeure and its juridical implications in bank credit agreements. The purpose of this study is to find out the juridical basis of whether COVID-19 can be used as an excuse for force majeure in bank credit agreements. The research method used is empirical normative with primary data sources through interviews at Bank Jateng and secondary data in the form of legal materials. Data collection techniques with interviews and literature study. The results of the study show that the Covid-19 pandemic, although as a non-natural disaster that meets the force majeure clause, does not necessarily become a reason for canceling the debtor's obligations in the credit agreement because it is not mentioned in the agreement regarding the Covid-19 pandemic condition and also the condition of the Covid-19 pandemic is a force.